2020
DOI: 10.6018/turismo.426101
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between service quality, client satisfaction, perceived value and client loyalty: a case study of Fly Emirates

Abstract: La lealtad del cliente es uno de los mayores desafíos para la industria de las aerolíneas. Por eso, los profesionales de marketing están buscando información sobre cómo desarrollar la lealtad del cliente. Este estudio explorará la relación entre la calidad del servicio, la satisfacción del cliente, el valor percibido y la lealtad del cliente en la industria aérea. El propósito de este estudio es desarrollar e implementar un método para que la aerolínea identifique atributos que aumentarán la lealtad del client… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 63 publications
0
10
0
Order By: Relevance
“…Submitted that adopting effective waste management strategies such as recycling and composting could reduce the emission of greenhouse gases. Previous research on the use of green hotels have shown a clear positive correlation between green confidence and green practices, which entail efficient communication of sustainability ( Jahmani et al, 2020;Kauppila et al, 2009;Lőrincz et al, 2022;Myers et al, 2011).…”
Section: Literature Reviewmentioning
confidence: 96%
“…Submitted that adopting effective waste management strategies such as recycling and composting could reduce the emission of greenhouse gases. Previous research on the use of green hotels have shown a clear positive correlation between green confidence and green practices, which entail efficient communication of sustainability ( Jahmani et al, 2020;Kauppila et al, 2009;Lőrincz et al, 2022;Myers et al, 2011).…”
Section: Literature Reviewmentioning
confidence: 96%
“…Previous studies by those carried out by Mohammed & Al-Swidi (2019) found that perceived value increases the loyalty of hotel customers. Perceived values can affect bank customer loyalty, according to Hamouda (2019) Perceived value can also affect customer loyalty, according to Molinillo et al, (2021) and Jahmani et al(2020). Based on the discussion, the following hypothesis was put forward: H1 : customer perceived value significantly affects consumer loyalty…”
Section: The Influence Of Customer Perceived Value On Consumer Loyaltymentioning
confidence: 99%
“…Familiarity refers to "the amount of product-related interactions acquired," on the other hand expertise is defined as "the capacity to execute effective productrelated activities" (Darko et al, 2020). Consumers interested in acquiring more product awareness, perform an efficient quest of details, keeping in mind the qualities of utility and being able to differentiate between products and better selectors of brands (Jawabreh et al, 2020;Jahmani et al, 2020).…”
Section: Knowledge About Renewable Energy Productsmentioning
confidence: 99%